Needs Analysis Study of Blended Learning Model to Improve Communication for Students with Hearing Impairment: Studi Analisis Kebutuhan Model Pembelajaran Blended Learning untuk Meningkatkan Komunikasi Siswa dengan Gangguan Pendengaran - Utami, Iga Setia; Budi, Setia; Arnez, Gaby; Hafid, Afdhil (Pedagogia : Jurnal Pendidikan, 2024)
This study aims to analyze the need to develop a blended learning model that can enhance and facilitate students with hearing impairment communication in learning. Because of their barriers, students with hearing loss have challenges in developing communication skills. So educational institutes must implement a learning model that accommodates their demand. This research covered a needs analysis to identify the problems and challenges faced by deaf students in communication and analyze their perspectives and expectations of appropriate learning models. The study involved five students with hearing barriers enrolled in college. Data was collected through qualitative and quantitative approaches. According to research, a blended learning model must be established that considers the demands of deaf students for them to adapt communication in their learning. Highlights: Blended learning: Integration of online and traditional teaching methods caters to diverse learning needs. Hearing impairment: Understanding unique challenges faced by students with hearing loss is crucial for effective education. Communication skills: Developing accessible communication strategies enhances learning outcomes for deaf students. Keywords: Blended Learning, Communication Skill, Hearing Impairment